ANALISIS OTORITAS PEMERINTAH DALAM PENETAPAN AWAL BULAN QOMARIAH - Marni, Marni; Hilal, Fatmawati (HISABUNA: Jurnal Ilmu Falak, 2021)
Abstract : Analysis of government authorities in determining the beginning of the lunar month. The aims of this study are: 1) To find out the method of determining the beginning of the lunar month in Indonesia, 2) To be able to find out the government's obstacles in determining the beginning of the lunar month, 3) To analyze the government's authority in determining the beginning of the lunar month. In answering these problems, the author uses a syar'i approach and an astronomical approach. This research is classified as library research, data is collected by quoting, adapting, and analyzing representative literature that has relevance to the problems discussed, then reviews, and concludes. After discussing the analysis of government authority in determining the beginning of the lunar month, the authors can conclude that it is very important to study more deeply about astronomy, especially regarding the determination of the beginning of the lunar month, in determining the beginning of the lunar month using two methods, namely the reckoning and rukyat methods, and in the initial determination of the government's version of the lunar month. Considering in the process of determining the beginning of the lunar month, there are often differences among Muslims. The implication of the research in this thesis is that the problem of differences that occur in determining the beginning of the month in Indonesia is due to differences in criteria for the new moon. This is to be able to broaden the understanding of how the method of determining the beginning of the lunar month in Indonesia and the criteria for determining the beginning of the lunar month used by the government. Reviewers and observations are expected to be carried out continuously in order to develop knowledge while still paying attention to their respective procedures, especially studies regarding the determination of the beginning of the lunar month. The author hopes that in the future the government will provide more direction or socialize to the surrounding community about what method to use so that if there is no difference in the process of determining the beginning of the lunar month. Keywords : Government Authority, Determining the Beginning of the Lunar Month Abstrak : Analisis otoritas pemerintah dalam penetapan awal bulan qomariah. Penelitian ini bertujuan untuk: 1) dapat mengetahui metode penentuan awal bulan qomariah di Indonesia, 2) dapat mengetahui kendala penetapan awal bulan qomariah oleh pemerintah, 3) menganalisis otoritas pemerintah dalam penetapan awal bulan qomariah. Penulis memakai pendekatan syar’i dan pendekatan astronomi untuk menjawab permasalahan tersebut. Penelitian ini termasuk library research, data dikumpulkan melalui kutipan, menyadur, dan melakukan analisis literatur secara representatif dan mempunyai relevansi terhadap pembahasan permasalahan, selanjutnya melakukan ulasan, dan menarik kesimpulan. Sesudah melakukan pembahasan tentang Analisis otoritas pemerintah dalam penetapan awal bulan qomariah, selanjutnya penulis dapat menyimpulkan bahwa sangat penting untuk mengkaji lebih mendalam mengenai ilmu falak, terutama mengenai penentuan awal bulan qomariah, menentukan awal bulan qomariah melalui dua metode yaitu metode rukyat dan hisab, serta menentukan awal bulan qomariah versi pemerintah. Mengingat proses penetapan awal bulan qomariah sering terjadi adanya perbedaan dikalangan umat muslim. Implikasi penelitian dalam skripsi ini ialah bahwa permasalah penetapan awal bulan yang berbeda di Indonesia karena perbedaan kriteria terhadap hilal. Hal ini untuk dapat memperluas wawasan pemahaman mengenai bagaimana metode penetapan awal bulan qomariah di Indonesia serta kriteria penetapan awal bulan bulan qomariah yang digunakan pemerintah. Pengkaji dan observasi diharapkan dapat dilakukan secara terus menerus demi mengembangkan pengetahuan dengan tetap memperhatikan prosedurnya masing-masing, terutama pengkajian mengenai penetapan awal bulan qomariah. Penulis berharap kedepannya pemerintah lebih memberikan arahan atau mensosialisasikan kepada masyarakat sekitar mengenai metode apa yang digunakan agar sekirannya tidak terjadi perbedaan dalam proses penetapan awal bulan qomariah. Kata kunci :Otoritas Pemerintah, Penetapan Awal Bulan Qomariah